The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/dote.12223
|View full text |Cite
|
Sign up to set email alerts
|

Cameron lesions in patients with hiatal hernias: prevalence, presentation, and treatment outcome

Abstract: Background and study aims Cameron lesions, as defined by erosions and ulcerations at the diaphragmatic hiatus, are found in the setting of gastrointestinal (GI) bleeding in patients with a hiatus hernia (HH). The study aim was to determine the epidemiology and clinical manifestations of Cameron lesions. Patients and methods This is a retrospective cohort study evaluating consecutive patients undergoing upper endoscopy over a two year period. Endoscopy reports were systematically reviewed to determine presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
1
21
0
7
Order By: Relevance
“…We also found that the prevalence of Cameron ulcers increases with size of HH. Our overall prevalence of 8.5% significantly increased to 17.5% for those with HH size ≥ 6 cm, which is similar to an observation by Gray et al [5]. Association between iron deficiency anaemia and Hiatal hernia has been described in literature [9,10].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that the prevalence of Cameron ulcers increases with size of HH. Our overall prevalence of 8.5% significantly increased to 17.5% for those with HH size ≥ 6 cm, which is similar to an observation by Gray et al [5]. Association between iron deficiency anaemia and Hiatal hernia has been described in literature [9,10].…”
Section: Discussionsupporting
confidence: 90%
“…Other hypothesized factors include mucosal ischemia/mucosal injury from acid reflux/NSAID use [1,5,6]. From our study, we found that large hiatal hernias are significantly associated with Cameron ulcer in the multivariate analysis; other factors such as NSAID/anticoagulant use/H.…”
Section: Discussionmentioning
confidence: 62%
“…Overall prevalence of Cameron lesions in all EGD's is less than 1% [6]. In a study by Camus et al of 3960 endoscopies, Cameron lesions were found only in 0.6% cases [7]. They are found in 5.2% of all hiatal hernias on EGD [8].…”
Section: Discussionmentioning
confidence: 95%
“…Their prevalence increases with the size of the hiatal hernia. Gray et al classified hiatal hernia according to size as follows: small (<3 cm), medium (3-4.9 cm) and large (>/=5 cm) [7]. Of all the Cameron lesions they found, 23.2% occurred in small, 32.6% occurred in medium and 44.2% occurred in large hiatal hernias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation